Assessing English Learners in Various Ways - Arny Irhani Asmin (Universitas Cokroaminoto Palopo, 2016)
This study aimed to know the implementation of a new test design given by the lecturer in English for Media class and to find out the perceived impacts by the students related to the tests given. A new way mentioned here is a lecturer gives freedom to the students to choose their own material to be presented or practice in the final test. The writer found that, this new way is success in reducing the students’ tensions in facing the final test; it could be seen from the process and the results of the test that are quite good. Moreover, in the process of the test, all students are excited in selecting and preparing materials to be presented in the test. Moreover, based on the results of direct observation and interviews to the students, the writer concluded that the implementation of this test creates a good atmosphere; fun and the tension level of students are also lighter. This brings a positive impact on the students, where the results obtained by the students in this test were also better than the previous test. In other words, by providing many options to the students in the test is better than only giving one choice to do.